Analisis Pembelajaran PAI Berbasis Standar Nasional Pendidikan (SNP) di SMP NU Muara Sugihan - M. Quzzan Azizi; Ali Imron; Ahmad Fauzi (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study aims to analyze Islamic Religious Education (PAI) learning at SMP NU Muara Sugihan from the perspective of the National Education Standards (SNP), focusing on the integration of NU values. A qualitative approach was employed, with data collected through in-depth interviews, observation, and school documentation. The findings indicate that the school curriculum adopts the Merdeka Curriculum combined with local content of kitab kuning, so that learning emphasizes not only academic mastery but also the development of religious character, moral integrity, and tolerance. The learning process is conducted collaboratively involving teachers, the principal, staff, parents, and students, supported by routine spiritual activities such as congregational Dhuha prayers. The assessment system integrates formative, summative, and religious practice-based evaluations. These results demonstrate that value internalization at SMP NU Muara Sugihan is effective, consistent with the internalization value theory of Muhammad Alim and Ahmad Tafsir, and supports the balanced achievement of students’ academic, spiritual, and social competencies. Practically, the findings can serve as a model for NU-based schools in designing curriculum, learning strategies, and value-based extracurricular activities.